The relationship between individual factors and organisational support with career development at UMLAND Berhad - Abbas, Salasiah (2014)
Today’s employment scenario presents changes in people’s career attitudes and experiences. Employees now prefer to work independently and be in control of their own career choice. Employers face competition and challenges to keep up with employees demand in providing them foreseeable career path, training and development. In this study, the researcher intends to identify the relationship between career planning and training and development in the organization with career development, and also to examine the relationship between self-efficacy and career autonomy with career development in UMLand Berhad. A total of 122 employees from two subsidiaries of UMLand in Johor were included in this parameter of study. The respondents were working across a wide spectrum of jobs which ranged from managerial functions to variety of sales and project oriented duties. Sampling method used was total population survey method. Sources of data for this research are gathered from primary data through questionnaires and secondary data through library research facilitates fabrication and company documents. Data was analysed using the SPSS 16.0 software and by using the inferential method (Spearman Correlation) to answer the objectives of this study. Spearman correlation analysis shows that career planning and training development factors are not significantly related to career development while self efficacy and career autonomy factors are significantly related to career development in UMLand Berhad. In other words, research findings show that there is no relationship between career planning and training and development with career development at UMLand. However, the findings show there is relationship between self-efficacy and career autonomy with career development at UMLand.